Technical and non-technical challenges for the Lungmen nuclear power plant project in Taiwan. (2nd October 2020) - Liu, Tai-Yi; Chen, Po-Han; Chou, Nelson N. S.; Hsieh, Ting-Ya
ABSTRACT: The Lungmen Nuclear Power Plant (LNPP) Project is the fourth nuclear power plant project in Taiwan, with two sets of 1, 350 MW Advanced Boiling Water Reactors designed by General Electric Company (GE). This project, with a planned construction duration of six years, was extended to seventeen years due to political issues, protests, and other interference. The construction work of the project was completed, with the contract terminated, on 31 May 2015. Although the LNPP project, besieged with controversy, was successfully and safely delivered, it was forced to 'stop and store' by the government after extreme anti-nuclear protestations. The technical (cost, schedule, QA/QC, etc.) and non-technical (stakeholder communication) challenges faced in this project are herein addressed. Project management methods are adopted to handle and review the results of resolution of the challenges. The contribution of this paper includes: (1) disclosing the construction management system of the LNPP project; (2) sharing solutions to the technical and non-technical challenges; and (3) learning lessons from the lack of public communication. The conclusions and suggestions proposed might be of help to activating the LNPP, as well as for other nuclear power plant projects under similar situations in Taiwan and beyond.